2001
DOI: 10.1107/s1600536801019365
|View full text |Cite
|
Sign up to set email alerts
|

Tripotassium hexahydrogen hexamolybdocobaltate(III) heptahydrate, K3[H6CoMo6O24]·7H2O

Abstract: The very stable title crystals, K3[H6CoMo6O24]·7H2O, that include the well known B‐type Anderson–Evans heteropolyoxometalate, were obtained by recrystallization of powder K3[H6CoMo6O24]·nH2O at pH 3.5. The unit cell consists of two different crystallographically discrete [H6CoMo6O24]3− polyanions. The two anions have the Co atoms at inversion centers and have close to m symmetry, with Co—O bond lengths in the range 1.898 (3)–1.912 (3) Å, Mo—O bond lengths in the ranges 1.700 (4)–1.726 (4), 1.895 (3)–1.960 (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Anderson-Evans cluster, as it has been known since, is made of six edge-shared distorted {MoO 6 } octahedra and the central cavity thus formed is occupied by slightly flattened, X(OH) 6 , heteroatom octahedron. The cluster assumes a near D 3d symmetry with dimensions ~8.6 × 8.6 × 2.7 Å and has been isolated with fifteen different heteroatoms till now [X: Al (Lee et al, 1991; Manikumari et al, 2002; Shivaiah et al, 2002; Martin et al, 2004; Shivaiah and Das, 2005; Liu et al, 2006; Dhara et al, 2007; Cao et al, 2008; Zhou et al, 2009), Cr (Perloff, 1970; An et al, 2006; Yu et al, 2006; Lee, 2007; Zhou and Yang, 2007; Shi D. et al, 2008; Shi D. M. et al, 2008; Zhang et al, 2008, 2014; Singh et al, 2010b, 2014; Li et al, 2011; Singh and Ramanan, 2011; Kumar et al, 2014a; Joo et al, 2015), Mn (He et al, 2012; Oms et al, 2012; Rosnes et al, 2012, 2013; Yan et al, 2012; Zhang et al, 2012, 2015a,b; Hutin et al, 2013; Ai et al, 2014; Yvon et al, 2014), Fe (Wu et al, 2001), Co (Nolan et al, 1996; Panneerselvam et al, 1996; Lee and Joo, 2000a; Lee et al, 2001; Martin et al, 2004), Ni (Lee et al, 2002; Liu et al, 2007; Liu F.-X. et al, 2008), Cu (Ito et al, 1989), Zn (Allen et al, 1997), Ga (Mensinger et al, 2008; Himeno et al, 2009), Te (Evans, 1948; Kondo et al, 1980; Robl and Frost, 1993a,b; Lorenzo-Luis et al, 1999; Drewes et al, 2004a,b; Charushnikova et al, 2005; Drewes and Krebs, 2005; Gao et al, 2007; Liu Y. et al, 2008; Yan et al, 2008), Rh (Ozawa et al, 1991), Pd (Ozawa et al, 1991), Sb (Ogawa et al, 1988; Yan et al, 2014), I (Kondo et al, 1980; Rosu and Weakley, 2000; An et al, 2...…”
Section: Introductionmentioning
confidence: 99%
“…Anderson-Evans cluster, as it has been known since, is made of six edge-shared distorted {MoO 6 } octahedra and the central cavity thus formed is occupied by slightly flattened, X(OH) 6 , heteroatom octahedron. The cluster assumes a near D 3d symmetry with dimensions ~8.6 × 8.6 × 2.7 Å and has been isolated with fifteen different heteroatoms till now [X: Al (Lee et al, 1991; Manikumari et al, 2002; Shivaiah et al, 2002; Martin et al, 2004; Shivaiah and Das, 2005; Liu et al, 2006; Dhara et al, 2007; Cao et al, 2008; Zhou et al, 2009), Cr (Perloff, 1970; An et al, 2006; Yu et al, 2006; Lee, 2007; Zhou and Yang, 2007; Shi D. et al, 2008; Shi D. M. et al, 2008; Zhang et al, 2008, 2014; Singh et al, 2010b, 2014; Li et al, 2011; Singh and Ramanan, 2011; Kumar et al, 2014a; Joo et al, 2015), Mn (He et al, 2012; Oms et al, 2012; Rosnes et al, 2012, 2013; Yan et al, 2012; Zhang et al, 2012, 2015a,b; Hutin et al, 2013; Ai et al, 2014; Yvon et al, 2014), Fe (Wu et al, 2001), Co (Nolan et al, 1996; Panneerselvam et al, 1996; Lee and Joo, 2000a; Lee et al, 2001; Martin et al, 2004), Ni (Lee et al, 2002; Liu et al, 2007; Liu F.-X. et al, 2008), Cu (Ito et al, 1989), Zn (Allen et al, 1997), Ga (Mensinger et al, 2008; Himeno et al, 2009), Te (Evans, 1948; Kondo et al, 1980; Robl and Frost, 1993a,b; Lorenzo-Luis et al, 1999; Drewes et al, 2004a,b; Charushnikova et al, 2005; Drewes and Krebs, 2005; Gao et al, 2007; Liu Y. et al, 2008; Yan et al, 2008), Rh (Ozawa et al, 1991), Pd (Ozawa et al, 1991), Sb (Ogawa et al, 1988; Yan et al, 2014), I (Kondo et al, 1980; Rosu and Weakley, 2000; An et al, 2...…”
Section: Introductionmentioning
confidence: 99%
“…2-8 On the other hand, a number of Anderson-type Mo VI complexes, [M(OH) 6 Mo 6 O 18 ] 3/4have already been prepared from aqueous solution. [18][19][20][21][22][23][24][25][26][27] In fact, the present study found the formation of [Ga(OH) 6 Mo 6 O 18 ] 3in aqueous Mo VI -Ga III system (pH 1.3-5). Thus, a cis-MoO 2 arrangement is usually found for the polyoxomolybdate structure.…”
Section: Discussionmentioning
confidence: 53%
“…† It is known that Anderson complexes with Cr III , Al III and Co III as the central heteroion are also hexaprotonated. 23,26,27 The present structure was isostructural with that of K 3 [Co(OH) 6 Mo 6 O 18 ]•7H 2 O, 25 and exhibited a slightly smaller monoclinic cell than the latter (2879.4(6) A ˚3 for Ga and 2881.5(9) A ˚3 for Co).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The positions of two NH 4 + cations found in the structure of (I) are close to positions of the K cations found in the structure of K 3 [Co(µ 3 -OH) 6 Mo 6 O 18 ] . 7H 2 O (Lee et al, 2001), but the position of the third one is different against the positions of the third K cation in the potassium compound. Both structures crystallize in the same space groups and exhibit similar lattice parameters of the unit cells.…”
Section: S3 Refinementmentioning
confidence: 93%